Yangon Peri-urban Livestock Survey 2019 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
The Yangon Peri-urban Livestock Survey, conducted in 2019, sampled commercial livestock farms within a 100 km radius of central Yangon. In the absence of any publicly available registry of livestock farms, a sample frame was developed by analyzing satellite images to identify the location of poultry-fish farms. A complete listing of livestock farms was conducted in all selected villages. The minimum size for inclusion of poultry farms in the survey was set at 500 chickens per farm, as the survey was designed to capture information on commercial farming operations. All farms in selected villages at or above this threshold were selected with 100% probability. The survey questionnaire was designed to collect detailed information on farm production practices and production economics. Interviews were conducted face to face with farm owners by trained enumerators on the respondents' farms. The final dataset is comprised of data from 513 farms, of which 423 chicken farms.